Land reform and rural livelihoods of evicted farm workers: a case study of Radway Green Farm Project - Zishiri, Kudzanai (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The land issue has remained a contentious one more than two decades into a democratic South Africa. With the dispossession of the indigenous people from their land stretching back as far as 1913, eviction of farm workers and farm dwellers has increased tremendously even in the post-Apartheid era. Thus, the main goal of this study is to analyse the impact of the eviction on the Radway Green farm workers' community and to examine the factors affecting the generation of livelihood activities in their new settlement. In doing so, I used the Sustainable Rural Livelihoods Approach (SRLA) as my theoretical framework as it conceptually grounds my area of study. It was employed to analyse data gathered from the field through in-depth interviews, focus groups, key informant interviews and descriptive observation of the case study. The centrality of the SRLA concept is on rural development, poverty eradication and the ability or sustainability of the vulnerable and poor to cope with stresses and shocks as they make a living (Scoones, 1998: 5). In that regard, the theoretical framework became an important cornerstone in analysing the impact of eviction of the Radway Green farm workers' community and examining the factors affecting the generation of livelihoods activities in their new settlement. To analyse the research findings, various themes were utilised Forced Evictions and Resettlement; Eviction or Displacement; The Struggles of Recreating Livelihoods; The Need for Security of Land Tenure and Access to Infrastructure. Under these themes, the study revealed how the eviction was detrimental to the livelihoods of the farm workers and farm dwellers as they lost the land that was a primary source for the construction of their livelihoods. They lost employment, homes, agricultural land for food security and natural resources, social and family structures and most importantly cultural disruption. It is well documented that the rural poor who constitute the farm workers and the farm dwellers are some of the vulnerable people who need constant governmental support through the promulgation of laws that protect them and assist in livelihood construction. Thus, this study also served to examine how the evicted workers and their families have settled into their new homes and how they, in conjunction with the Department of Rural Development and Land Reform and any other government agencies are faring in terms of the establishment of income generating projects for their livelihoods at the new settlement.
Keywords: Uncatalogued